Analisis Kesiapan SDM dalam Pengembangan Karir Karyawan pada Unit PKP-PK di UPBU Tebelian Sintang - Ronaldy Candra Septyanto; Walid Jumlad (Pusat Riset dan Inovasi Nasional, 2023)
Human resource readiness is an important asset and is the main determining factor in the performance of all activities and institutional activities, so that it can support employee career development. Career development is very important to support life achievements and quality of life as well as job satisfaction with each individual's current achievements. There are two factors in career development that can determine a person's career success, namely internal factors including motivation to progress, intellectual ability, interpersonal skills, level of education, and work experience. Meanwhile, factors that come from outside are the attitude of superiors, the weight of work, job vacancies and work productivity. The aim of this research is to determine the personal readiness of HR in the PKP-PK unit in career development at UPBU Tebelian Sintang and to find out the process, obstacles and solutions regarding HR readiness in career development at the unit (PKP-PK) at UPBU Tebelian Sintang. This study uses a qualitative method. The data collection techniques used were observation, interviews and documentation. The respondents in this research were PKP-PK unit personnel at UPBU Tebelian Sintang. The observations in this research were to conduct reviews and observations at the PKP-PK unit at UPBU Tebelian Sintang. The documentation in this research is activities that occurred in the PKP-PK area at UPBU Tebelian Sintang. The results of the discussion in this research are that Readiness is a process or action carried out by a person to be ready to change or respond to something that can make them ready to provide a certain response or response to a situation and employees in the PKP-PK unit have provided information that their level of readiness is sufficient. far above average. Because it is able to prepare quality human resources who are willing to continue learning and developing themselves and Tebelian Sintang Airport has stages of career development in the Aviation Accident Relief and Fire Fighting (PKP-PK) unit, namely through a proposal process from superiors to be registered and get a queue where there will be further information if there is a call in the queue and then the names that come out must be ready to carry out training to support career development at the PKP-PK unit at Tebelian Sintang Airport.